Effect of n-Butyl-2-Cyanoacrylate on High-Risk Colonic Anastomoses - Huseyin Ayhan Kayaoglu; Omer Faik Ersoy; Namik Ozkan; Alper Celik; Nurper Onuk Filiz (Kaohsiung Journal of Medical Sciences, 2009)
We investigated the effect of n-butyl-2-cyanoacrylate (BCA) on colonic anastomosis under clean contaminated procedure (CCP) and bacterial peritonitis (BP) conditions in rats. Male Wistar albino rats (n = 80) were divided into two groups: CCP and BP. In the CCP group, colonic resection and anastomosis were performed. BP was induced by cecal ligation and puncture. BCA was administered to the anastomosis in half of the rats in both groups. Anastomotic assessment was done on postoperative days 3 and 7 by evaluating the burst pressure, and gross anastomotic and histopathologic healing indices. The presence and severity of adhesion formation was also investigated. There were no differences in terms of gross healing parameters on days 3 and 7. Burst pressures were also similar on both days (p = 0.244 and p = 0.101, respectively). In the early phase (day 3), adhesion development (p < 0.001), granulocytic cell infiltration (p = 0.02), inflammation (p = 0.019) and necrosis (p = 0.019) were higher in the BCA groups. Mononuclear cell infiltration (p = 0.659), fibroblastic cell infiltration (p = 0.538) and capillary formation (p = 0.316) were similar. In the late phase (day 7), adhesion development (p < 0.001), necrosis (p = 0.001) and granulocytic cell infiltration (p = 0.034) were higher in the treatment groups. Fibroblastic cell infiltration (p = 0.017) and capillary formation (p = 0.016) were lower in BCA treated rats, particularly in the BP condition. Mononuclear cell infiltration did not differ (p = 0.176). The application of BCA did not provide any benefit under either CCP or BP conditions. Moreover, BCA caused increased inflammatory reactions, necrosis and adhesion formation. During the late phase of healing, the ongoing enhanced inflammation caused a reduction in capillary formation and fibroblastic infiltration, particularly under BP conditions.